Collaborative Governance Dalam Proses Penanggulangan Bencana Alam Di Kabupaten Lembata Provinsi Nusa Tenggara Timur - Lango Kukun, Syamsudin; Subiyakto, Rudi; Akhyary, Edy (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2024)
The Lembata Regency Government uses government cooperation as the main method for dealing with natural disasters. The creation of strategic disaster documents such as disaster risk assessment documents and disaster contingency plans shows collaborative Governance successfully handled the disaster in Lembata Regency. This research aims to find out about Collaborative Governance in Natural Disaster Management in Lembata Regency, East Nusa Tenggara. This research uses a qualitative descriptive research method. Primary and secondary data are data sources for this research. Research results (1) indicators of face-to-face dialogue in collaboration are key elements of effective disaster management, (2) indicators of building trust between Stakeholders is an important component to achieve optimal results in mitigation efforts and response to disasters, (3) indicators of commitment to the process become a solid foundation in joint efforts to overcome disasters, (4) indicators of shared understanding are needed to build effective disaster management cooperation and successful in Lembata Regency, (5) interim results indicators of this collaboration have a strategic impact and are an important step towards more effective and successful disaster management in Lembata Regency. In conclusion, to achieve this goal, inclusive and structured collaboration is needed with a clear division of roles and responsibilities.